Legal Responsibility of Entrepreneurs in Cases of Violation of Micro-Small Business Permits (IUMK) for Karak Crackers in Gadingan Village, Mojolaban District - Dinda Shafa Tiara Rusli; Arief Budiono; Nurul Hidayati; Luthfiyyah Amalina Husna; Arief Isdiman Saleh (Universitas Muhammadiyah Surakarta, 2026)
This research is motivated by the continued discovery of violations of the legal obligations of Micro and Small Business Permits (IUMK) by karak cracker entrepreneurs in Gadingan Village, Mojolaban District, which have the potential to result in legal liability consequences and hinder business protection and development. The purpose of this study is to determine and analyze the form of legal responsibility of karak cracker entrepreneurs in violation of business permits and to identify factors that cause low legal compliance of entrepreneurs with the obligation to have and comply with IUMK in Mojolaban Village. The research method used is empirical juridical legal research with a field approach through interviews, observations, and document studies of business actors and related agencies. The results of the study indicate that the legal responsibility of business actors for violations of IUMK in practice is mostly realized through guidance, assistance, and facilitation of permits by the local government, although normatively it is possible to apply administrative sanctions. In addition, low legal compliance is influenced by internal factors such as limited legal understanding, the perception that permits are not yet urgent, and digital literacy constraints, and external factors such as uneven socialization, weak supervision, lack of firm sanctions, and the strength of traditional business culture that has been passed down through generations.